Perspective and perspectivation in discourse - Graumann, Carl F.; Kallmeyer, Werner (J. Benjamins Pub. Co, 2002)
'Perspective' and 'viewpoint' are widely used in everyday talk as well as in the specialist languages of the social, cognitive, and literary sciences. Taken from the field of visual perception and representation, these concepts have acquired a general meaning and significance, as characteristics of human cognitive processing. Since, however, this field is shared by an increasing body of disciplines, perspective terms have also acquired specific and technical meanings. A striking example is the newly introduced use of 'perspectivation' in discourse analysis. This volume on 'perspective and persp
Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic books; Aufsatzsammlung; Perspektivierung; Konversationsanalyse